Kontribusi Penggunaan Literasi Digital Terhadap Peningkatan Hasil Belajar Pendidikan Agama Islam Siswa Di SMK Pawiyatan Surabaya - Bachtiar Hariyadi; Yuli Astutik; Chusnul Chotimah; Fatimatuzzahro Fatimatuzzahro (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This study examines the use of digital literacy to increase the learning outcomes of PAI students at SMK Pawiyatan Surabaya. This study uses quantitative research with a correlational descriptive approach. Data collection using a questionnaire was carried out in a self-administered questionnaire, namely, the respondents answered the questionnaire themselves that had been made by the researcher. The sample used was 177 students as respondents. Hypothesis testing was carried out using the Partial Least Square (PLS) based Structural Equation Model (SEM) approach using the Smart PLS application version 3.0. The results showed that the ability to access digital tools (XI), the ability to search for information with digital devices (X2), and the ability to evaluate information from the Internet (X3) both partially and simultaneously had a significant positive effect on PAI learning outcomes (Y). Digital literacy skills are very important in learning, especially in finding PAI information with digital tools. The more professional students are in search for this information, their insights and knowledge references will increase so that student learning outcomes for PAI will also increase.